Exploratory Factor Analysis of the Motivation Scale for Qur’an Memorization in Islamic Higher Education - Rena, Syahidah (LETIGES, 2026)
This study aims to test and establish the construct validity of the Qur'an memorization motivation scale based on a literature review using the Exploratory Factor Analysis (EFA) method. Specifically, this study also aims to test the extent to which the statistical model of Qur'an memorization motivation that has been built by various previous studies, both quantitative and qualitative—which divides the motivation to memorize the Qur'an into two latent variables (intrinsic and extrinsic) with a number of manifest variables—can fit the empirical data. This study uses a quantitative research design to build a Qur'an memorization motivation scale through exploratory factor analysis involving 154 students of the Institute of Qur'anic Sciences (IIQ) Jakarta as respondents. Descriptive analysis was conducted before the factor test, and this instrument will be revalidated in subsequent studies using Confirmatory Factor Analysis (CFA). The results of the study showed that EFA successfully identified six motivational factors with adequate psychometric characteristics: external recognition (7.576/30.305%), internal spirituality (2.874/11.495%), external environment (1.746/6.984%), family support (1.289/5.157%), teacher and peer support (1.240/4.959%), and hope for reward in the afterlife (1.103/4.413%). Initial construct validity was supported by a KMO value of 0.840, a significant Bartlett test (χ² = 1743.881; p < 0.001), and a total explained variance of 63.31%. These findings confirm that the motivation to memorize the Qur'an is a multidimensional construct that includes intrinsic and extrinsic aspects. In addition, EFA proved effective as an initial psychometric approach in building the validity structure of the instrument, which will be the basis for the further validation process through CFA.